PROFIL KLINIS BENIGN ROLANDIC EPILEPSY (BRE) DI RSUD PASAR REBO TAHUN 2013-2018 - Donny Hamdani Hamid; Syairah Syairah; Syarly Melani; Astri Budikayanti (NEURONA, 2019)
CLINICAL PROFILE OF BENIGN ROLANDIC EPILEPSY (BRE) PASAR REBO GENERAL REGIONAL HOSPITAL 2013-2018ABSTRACTIntroduction: Benign rolandic epilepsy (BRE) is the most common focal epileptic syndromes in children, correlated with genetic abnormality, has unique clinical features and specific electroencephalogaphic (EEG) pattern. Most of BRE cases will remit spontaneously even without medication by puberty.Aims: To know the clinical profile of BRE and the association between electroencephalogaphic (EEG) pattern with and seizure types in BRE.Methods: Observational analytic cross-sectional study based on medical record of BRE cases in Pasar Rebo general regional hospital from January 2013–Desember 2018. Subjects were grouped into focal to bilateral tonic clonic seizure (group I) and focal onset seizures with impaired awareness (group II). Relationship between groups and hemispheric lateralization based on interictal epileptiform (unilateral or bilateral) using EEG was analyzed.Results: There were 22 subjects, average age of seizure onset was 7,86+2,3 years old with male-to-female ratio1,75:1. The majority of subjects (40.9%) had only received an EEG after more than 1 year of onset and only 6 (27.3%) subjects had done less than one month.. Amongst all subjects, 15 subjects (68,2%) already consumed anti epileptic drugs (AED), in which 11 subjects (73,3%) consumed valproic acid (VPA). Most common clinical features were hypersalivation and hemifacial sensorimotor symptoms with localization of interictal epileptiform discharges mainly in centro-temporal. There were no significant relationship between hemispheric lateralization of epileptiform discharge and type of seizure.Discussion: Most BRE subjects had onset of 7.86+2.3  years with the main symptoms of hypersalivation  and hemifacial sensorimotor symptoms, as well as localization of interictal epileptiform discharges especially in the centro- temporal.. There were no significant relationship between hemispheric lateralization of interictal epileptiform discharges and seizure type.Keywords: BRE, clinical profiles, epilepsy syndromesABSTRAKPendahuluan: Benign rolandic epilepsy (BRE) merupakan sindrom epilepsi fokal yang paling sering ditemukan pada anak kelompok usia 1-14 tahun, berhubungan dengan kelainan genetik, memiliki gambaran klinis dan EEG khas. Sebagian besar mengalami remisi tanpa obat pada usia pubertas.Tujuan: Mengetahui karakteristik profil klinis dan hubungan antara gambaran elektroensefalografi (EEG) dengan bentuk bangkitan pada BRE.Metode: Studi potong lintang analitik observasional menggunakan data rekam medispasien yang didiagnosis BRE di Klinik Saraf RSUD Pasar Rebo, Jakarta, periode Januari 2013 hingga Desember 2018. Subjek dikelompokkan menjadi tipe bangkitan awitan fokal yang berkembang menjadi tonik klonik bilateral (grup I) dan tipe bangkitan awitan fokal dengan gangguan kesadaran (grup II), yang dihubungkan dengan lateralisasi hemisferik aktivitas epileptiform interiktal (unilateral atau bilateral) pada EEG.Hasil: Dari 22 subjek, rasio perbandingan laki-laki:perempuan sebesar 1,75:1 dan rerata usia awitan bangkitan adalah 7,86+2,3 tahun. Mayoritas subjek (40,9%) baru dilakukan EEG setelah lebih dari 1 tahun dari awitan dan hanya 6 subjek (27,3%) yang dilakukan kurang dari satu bulan. Pada 15 subjek (68,2%) telah mengkonsumsi obat antiepilepsi (OAE) yang sebagian besar berupa asam valproat (73,3%). Gambaran klinis utama adalah hipersalivasi dan gejala sensorimotor hemifasial dengan lokalisasi cetusan epileptiform interiktal terutama di sentro-temporal. Tidak didapatkan hubungan bermakna antara lateralisasi hemisferik aktivitas epileptiform interiktal dengan bentuk bangkitan.Diskusi: Sebagian besar subjek BRE mengalami usia awitan bangkitan 7,86+2,3 tahun dengan gejala utama hipersalivasi dan gejala sensorimotor hemifasial, serta lokalisasi cetusan epileptiform interiktal terutama di sentro-temporal. Tidak didapatkan hubungan bermakna antara lateralisasi aktivitas epileptiform interiktal dengan jenis bangkitan pada BRE.Kata kunci: BRE, profil klinis, sindrom epilepsi